A phosphite catalyst system and preparation method thereof

By adding amine-cured epoxy resin as a solid stabilizer to the rhodium complexing catalyst of the phosphite ligand, the problem of decomposition of the phosphite ligand during the carbonylation process is solved, and the stability of the catalyst is improved and the process is simplified, making it easy for industrial application.

CN119771503APending Publication Date: 2025-04-08SHANDONG CHAMBROAD PETROCHEMICALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411963295.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Phosphite ligands are easily hydrolyzed and decomposed during carbonylation, resulting in a decrease in rhodium stability, and it is difficult for the prior art to effectively inhibit their decomposition.

Method used

A catalyst system for using a rhodium complexing catalyst containing phosphite ligand and an amine-cured epoxy resin as a solid stabilizer is used to combine N atoms in the epoxy resin with the acid produced by decomposition to achieve its removal and enhance the stability of rhodium.

Benefits of technology

It effectively inhibits the decomposition of phosphite ligands, improves the stability of the catalyst, avoids the loss of rhodium during water washing, and simplifies the process flow, making it convenient for industrial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217719930000021
    Figure BDA0005217719930000021
  • Figure BDA0005217719930000031
    Figure BDA0005217719930000031
  • Figure BDA0005217719930000041
    Figure BDA0005217719930000041
Patent Text Reader

Abstract

The present invention provides a phosphite catalyst system, comprising a rhodium complex catalyst containing a phosphite ligand and a solid stabilizer; the solid stabilizer is an amine-cured epoxy resin. Compared with the prior art, the present invention uses an amine-cured epoxy resin as a solid stabilizer, wherein the N atom containing a lone pair of electrons can be combined with the acid generated by the decomposition of the phosphite ligand, and after the combination, the amine-cured epoxy resin and the acid in the system can be removed by simple filtration separation, thereby enhancing the stability of the rhodium; and the amine-cured epoxy resin is insoluble in organic solvents, does not thermally decompose, has good thermal stability, is easy to obtain, and is convenient for industrial use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic synthesis, and in particular relates to a phosphite catalyst system and a preparation method thereof. Background Art

[0002] The liquid phase circulation method (i.e., the second-generation low-pressure rhodium method) jointly developed by UCC / Davy / Johnson Mattey was put into industrial application in 1984, and various research and development institutions and enterprises have continuously iterated and innovated the ligands. Phosphite is one of the more classic ligands in the current industrial application of carbonylation. Due to its unique electronic structure, phosphite ligands have good effects in catalyzing olefins, especially internal olefins. Dow's use of diphosphite ligands for the industrial production of 2-PH is the most classic industrial case of phosphite ligand-catalyzed carbonylation. However, due to the characteristics of the phosphite structure, it is easy to hydrolyze to produce hydroxyalkyl phosphoric acid, phosphorous acid or phosphoric acid, and the presence of acidic substances will further aggravate the decomposition of phosphite ligands, resulting in reduced rhodium stability. How to inhibit the decomposition of phosphite ligands has become a key issue in the industry.

[0003] Dow and other European and American companies have provided relevant solutions to the problem of phosphite stability. The US patent with patent number US5741944 uses aqueous buffer extraction to remove the acid in the reaction system at the overall industrial back end, inhibiting the further decomposition of the ligand and achieving enhanced ligand stability. The Chinese patent with publication number CN115850041B adds phenolic antioxidants to the catalytic system to achieve the purpose of increasing ligand stability by inhibiting the oxidation of phosphite ligands. However, the aqueous buffer washing method further introduces water, and the washing process may cause the loss of rhodium, while the addition of antioxidants or imidazole additives results in the addition of other substances into the system, which are difficult to remove. Summary of the invention

[0004] In view of this, the technical problem to be solved by the present invention is to provide a phosphite catalyst system and a preparation method thereof, which helps to inhibit the decomposition of the phosphite ligand and increase the stability of the catalyst.

[0005] The invention provides a phosphite catalyst system, comprising a rhodium complex catalyst containing a phosphite ligand and a solid stabilizer; the solid stabilizer is an amine-cured epoxy resin.

[0006] Preferably, the phosphite ligand is selected from monodentate phosphites and / or bidentate phosphites.

[0007] Preferably, the phosphite ligand has a structure shown in Formula A and / or Formula B:

[0008]

[0009] Preferably, the molar ratio of the phosphite ligand to the elemental rhodium in the rhodium complex catalyst containing the phosphite ligand is 1:1 to 20:1.

[0010] Preferably, the method further comprises an aldehyde solvent; the mass of the amine-cured epoxy resin is 0.1% to 2% of the total mass of the rhodium complex catalyst containing the phosphite ligand and the aldehyde solvent.

[0011] Preferably, the mass concentration of the rhodium complex catalyst containing the phosphite ligand and the elemental rhodium in the aldehyde solvent is 50 to 500 ppm.

[0012] Preferably, the aldehyde solvent is selected from one or more of butyraldehyde, valeraldehyde, hexanal and heptanal;

[0013] And / or, the amine-cured epoxy resin is selected from amine-cured bisphenol F epoxy resin and / or amine-cured bisphenol A epoxy resin.

[0014] Preferably, the rhodium complex catalyst containing the phosphite ligand is prepared according to the following method:

[0015] Under the condition of synthesis gas, a metal rhodium compound and a phosphite ligand are heated and reacted in an aldehyde solvent to obtain a rhodium complex catalyst containing the phosphite ligand.

[0016] Preferably, the temperature of the heating reaction is 60° C. to 100° C.; the time of the heating reaction is 0.5 to 2 h; and the pressure of the heating reaction is 1 to 3 MPa.

[0017] The present invention also provides a method for preparing a phosphite catalyst system, comprising the following steps:

[0018] Under the condition of synthesis gas, the metal rhodium compound and the phosphite ligand are heated to react in an aldehyde solvent, and after cooling, the synthesis gas is discharged and a solid stabilizer is added to obtain a phosphite catalyst system.

[0019] The present invention provides a phosphite catalyst system, comprising a rhodium complex catalyst containing a phosphite ligand and a solid stabilizer; the solid stabilizer is an amine-cured epoxy resin. Compared with the prior art, the present invention uses an amine-cured epoxy resin as a solid stabilizer, wherein the N atom containing a lone pair of electrons can be combined with the acid generated by the decomposition of the phosphite ligand, and after the combination, the amine-cured epoxy resin and the acid in the system can be removed by simple filtration separation, thereby enhancing the stability of the rhodium; and the amine-cured epoxy resin is insoluble in organic solvents, does not thermally decompose, has good thermal stability, is easy to obtain, and is convenient for industrial use. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0021] The invention provides a phosphite catalyst system, comprising a rhodium complex catalyst containing a phosphite ligand and a solid stabilizer; the solid stabilizer is an amine-cured epoxy resin.

[0022] According to the present invention, the phosphite ligand is preferably a monodentate phosphite and / or a bidentate phosphite.

[0023] Specifically, the phosphite ligand has a structure shown in Formula A and / or Formula B:

[0024]

[0025] According to the present invention, the molar ratio of the phosphite ligand to the elemental rhodium in the rhodium complex catalyst containing the phosphite ligand is 1:1 to 20:1; optionally, the molar ratio of the phosphite ligand to the elemental rhodium in the rhodium complex catalyst containing the phosphite ligand is 1:1, 2:1, 5:1, 8:1, 10:1, 12:1, 15:1, 18:1, 20:1 or a range between any two of the above values.

[0026] According to the present invention, the phosphite catalyst system further comprises an aldehyde solvent; the aldehyde solvent may be one or more of butyraldehyde, valeraldehyde, hexanal and heptanal; in the embodiments provided by the present invention, n-heptanal is specifically used as an example for illustration.

[0027] According to the present invention, the mass concentration of elemental rhodium in the rhodium complex catalyst containing phosphite ligand and aldehyde solvent is preferably 50-500ppm, more preferably 100-400ppm, further preferably 100-300ppm, further preferably 150-250ppm, and most preferably 200ppm.

[0028] According to the present invention, the rhodium complex catalyst containing phosphite ligand is preferably prepared according to the following method: under the condition of synthesis gas, a metal rhodium compound and a phosphite ligand are heated and reacted in an aldehyde solvent to obtain a rhodium complex catalyst containing phosphite ligand. Wherein, synthesis gas is a mixed gas with carbon monoxide and hydrogen as the main components, and the molar ratio of CO:H2 in the synthesis gas described in the present invention is preferably 1:1; the metal rhodium compound can be a metal rhodium compound well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably rhodium trichloride, rhodium acetate, carbonyl bis (triphenylphosphine) rhodium chloride, dicarbonyl acetylacetonate rhodium, 1,5-cyclooctadiene (acetylacetonate) rhodium, (acetylacetonate) carbonyl (triphenylphosphine) rhodium, hydrogenated carbonyl tri (triphenylphosphine) rhodium, bis (triphenylphosphine) chloride carbonyl rhodium, tri (triphenylphosphine) rhodium chloride and tetrakis (triphenylphosphine) One or more of rhodium hydride; the temperature of the heating reaction is preferably 60°C to 100°C, more preferably 70°C to 90°C, more preferably 75°C to 85°C, and most preferably 80°C; the time of the heating reaction is preferably 0.5 to 2h, more preferably 0.8 to 1.5h, and more preferably 1h; the pressure of the heating reaction is preferably 1 to 3MPa, more preferably 1.5 to 2.5MPa, and more preferably 2MPa; the pressure of the heating reaction is provided by synthesis gas; after the heating reaction is completed, it is preferably cooled to room temperature and the synthesis gas is discharged to obtain a rhodium complex catalyst containing a phosphite ligand and an aldehyde solvent.

[0029] According to the present invention, the amine-cured epoxy resin is preferably an amine-cured bisphenol F epoxy resin and / or an amine-cured bisphenol A epoxy resin.

[0030] According to the present invention, the amine curing agent of the amine-cured epoxy resin is preferably a fatty amine curing agent, which may be one or more of triethylenetetramine, tetraethylenepentamine and 3-dimethylaminopropylamine, more preferably triethylenetetramine.

[0031] In a specific embodiment provided by the present invention, the amine-cured epoxy resin has a structure as described in Formula C:

[0032]

[0033] Wherein, -R- is a group represented by formula a or formula b:

[0034]

[0035] In a specific embodiment provided by the present invention, the amine-cured epoxy resin is bisphenol F epoxy resin DER354.

[0036] According to the present invention, the mass of the amine-cured epoxy resin is preferably 0.1% to 2% of the total mass of the rhodium complex catalyst containing phosphite ligands and the aldehyde solvent, more preferably 0.5% to 1.5%, and even more preferably 0.5% to 1.0%; optionally, the mass of the amine-cured epoxy resin is preferably 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% of the total mass of the rhodium complex catalyst containing phosphite ligands and the aldehyde solvent, or the range between any two of the above values.

[0037] The present invention uses amine-cured epoxy resin as a solid stabilizer, wherein the N atom containing a lone pair of electrons can be combined with the acid generated by the decomposition of the phosphite ligand. After the combination, the amine-cured epoxy resin and the acid in the system can be removed by simple filtration separation, thereby enhancing the stability of rhodium. In addition, the amine-cured epoxy resin is insoluble in organic solvents, does not undergo thermal decomposition, has good thermal stability, is easy to obtain, and is convenient for industrial use.

[0038] The present invention also provides a method for preparing a phosphite catalyst system, comprising the following steps: heating a metal rhodium compound and a phosphite ligand in an aldehyde solvent for reaction under the condition of synthesis gas, discharging the synthesis gas after cooling, and adding a solid stabilizer to obtain the phosphite catalyst system.

[0039] The present invention has no special restrictions on the sources of all raw materials, and any raw materials available on the market can be used; the metal rhodium compound, phosphite ligand, aldehyde solvent and solid stabilizer are all as described above and will not be described in detail here.

[0040] Under the condition of synthesis gas, the metal rhodium compound and the phosphite ligand are heated to react in an aldehyde solvent, and the temperature of the heating reaction is preferably 60°C to 100°C, more preferably 70°C to 90°C, more preferably 75°C to 85°C, and most preferably 80°C; the time of the heating reaction is preferably 0.5 to 2h, more preferably 0.8 to 1.5h, and more preferably 1h; the pressure of the heating reaction is preferably 1 to 3MPa, more preferably 1.5 to 2.5MPa, and more preferably 2MPa; the pressure of the heating reaction is provided by the synthesis gas; after the heating reaction is completed, it is preferably cooled to room temperature, the synthesis gas is discharged, and a solid stabilizer is added to obtain the phosphite catalyst system.

[0041] The present invention adds an insoluble solid stabilizer into the reaction system, which can be separated by filtration, has a simple process and is easy to realize industrialization.

[0042] In the present invention, the phosphite catalyst system is heated under a protective atmosphere to evaluate stability; the protective atmosphere can be any protective atmosphere familiar to those skilled in the art without any particular limitation, and nitrogen is preferred in the present invention; the heating temperature is specifically 120° C.; and the heating time is specifically 20 h.

[0043] The present invention also provides a hydroformylation reaction, which is carried out by catalysis of the above-mentioned phosphite catalyst system.

[0044] More specifically, the raw material for the hydroformylation reaction is α-olefin.

[0045] In a specific embodiment provided by the present invention, the raw material for the hydroformylation reaction is 1-hexene.

[0046] In a specific embodiment provided by the present invention, the temperature of the hydroformylation reaction is 70°C to 90°C, more preferably 75°C to 85°C, and even more preferably 80°C.

[0047] In a specific embodiment provided by the present invention, the pressure of the hydroformylation reaction is 1.5-3 MPa, more preferably 2 MPa.

[0048] In order to further illustrate the present invention, a phosphite catalyst system and a preparation method thereof provided by the present invention are described in detail below in conjunction with examples; the bisphenol F type cross-linked network epoxy resin used in the examples is bisphenol F epoxy resin DER354.

[0049] The reagents used in the following examples are all commercially available.

[0050] Example 1

[0051] A 100mL stainless steel reactor was lined with polytetrafluoroethylene, and 20g of n-heptanal, 200ppm of dicarbonyl acetylacetonate rhodium, ligand A (the molar amount added was 10:1 compared to rhodium), and the syngas (CO: 50% v / v, H2: 50% v / v) was replaced three times. The reaction temperature was 80°C, the syngas pressure was 2MPa, and the reaction was performed for 1h to prepare the catalyst liquid. After the reaction was completed, the reaction was cooled to room temperature, the syngas was discharged, 0.1g of solid stabilizer bisphenol F type cross-linked network epoxy resin was added, and the reaction was replaced with nitrogen three times, and then the temperature was raised to 120°C and heated under a nitrogen atmosphere for 20h. After the reaction was completed, samples were taken to detect the rhodium concentration and ligand concentration. The experimental results are shown in Table 1.

[0052] Example 2

[0053] The experiment was carried out according to the method of Example 1, except that 0.2 g of a solid stabilizer, bisphenol F type cross-linked network epoxy resin, was added. The experimental results are shown in Table 1.

[0054] Example 3

[0055] The experiment was carried out according to the method of Example 1, except that 0.1 g of a solid stabilizer, bisphenol A type cross-linked network epoxy resin, was added. The experimental results are shown in Table 1.

[0056] Example 4

[0057] The experiment was carried out according to the method of Example 1, except that 0.2 g of a solid stabilizer, bisphenol A type cross-linked network epoxy resin, was added. The experimental results are shown in Table 1.

[0058] Example 5

[0059] The experiment was carried out according to the method of Example 1, except that ligand A was replaced by ligand B, and the added molar amount of ligand B was 5:1 compared with rhodium. The experimental results are shown in Table 1.

[0060] Example 6

[0061] The experiment was carried out according to the method of Example 5, except that 0.2 g of a solid stabilizer, bisphenol F type cross-linked network epoxy resin, was added. The experimental results are shown in Table 1.

[0062] Example 7

[0063] The experiment was carried out according to the method of Example 5, except that 0.1 g of a solid stabilizer, bisphenol A type cross-linked network epoxy resin, was added. The experimental results are shown in Table 1.

[0064] Example 8

[0065] The experiment was carried out according to the method of Example 5, except that 0.2 g of a solid stabilizer, bisphenol A type cross-linked network epoxy resin, was added. The experimental results are shown in Table 1.

[0066] Example 9

[0067] A 100mL stainless steel reactor was lined with polytetrafluoroethylene, and 20g of n-heptanal, 200ppm of dicarbonyl acetylacetonate rhodium, ligand A (the molar amount added was 10:1 compared to rhodium), and the synthesis gas (CO: 50% v / v, H2: 50% v / v) was replaced three times. The reaction temperature was 80°C, the synthesis gas pressure was 2MPa, and the reaction was carried out for 1h to prepare the catalyst liquid. Then the temperature was lowered, 10g of 1-hexene was added, the temperature was raised to 80°C, the pressure was raised to 2MPa, and the hydroformylation evaluation reaction was carried out for 2h. After the reaction was completed, the sample was taken for chromatographic analysis, and the 1-hexene conversion rate was 94.8%, and the aldehyde selectivity was 98.4%.

[0068] Example 10

[0069] A 100mL stainless steel reactor was lined with polytetrafluoroethylene, and 20g of n-heptanal, 200ppm of dicarbonyl acetylacetonate rhodium, ligand A (the molar amount added was 10:1 compared to rhodium), and the syngas (CO: 50% v / v, H2: 50% v / v) was replaced three times. The reaction temperature was 80℃, the syngas pressure was 2MPa, and the reaction was carried out for 1h to prepare the catalyst liquid. After the reaction was completed, the reaction was cooled to room temperature, the syngas was discharged, 0.2g of solid stabilizer bisphenol F type cross-linked network epoxy resin was added, and the reaction was replaced with nitrogen three times. Then the temperature was raised to 120℃, and the reaction was heated under nitrogen atmosphere for 20h. Then the temperature was lowered, 10g of 1-hexene was added, the temperature was raised to 80℃, and the pressure was 2MPa for hydroformylation evaluation reaction for 2h. After the reaction was completed, the sample was taken for chromatographic analysis, and the 1-hexene conversion rate was 94.3%, and the aldehyde selectivity was 98.5%. Compared with the fresh catalyst that had not been treated at 120℃ for 20h, the activity remained basically stable.

[0070] Embodiment 11

[0071] The experiment was carried out according to the method of Example 10, except that no solid stabilizer was added. After the evaluation of the return, the 1-hexene conversion was 48.9%, and the aldehyde selectivity was 89.6%. Compared with the fresh catalyst that had not been treated at 120°C for 20 hours, the activity was reduced by 48.4%.

[0072] Comparative Example 1

[0073] The experiment was carried out according to the method of Example 1, except that no solid stabilizer was added. The experimental results are shown in Table 1.

[0074] Comparative Example 2

[0075] The experiment was carried out according to the method of Example 5, except that no solid stabilizer was added. The experimental results are shown in Table 1.

[0076] The rhodium concentration in Table 1 was measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), and the ligand was measured by liquid chromatography.

[0077] Table 1 Catalyst stability results

[0078] Rhodium loss % Ligand loss % Rhodium Black Case Example 1 10 15 none Example 2 6 9 none Example 3 15 24 A small amount of rhodium black on the stirring paddle Example 4 9 12 none Example 5 18 27 A small amount of rhodium black on the stirring paddle Example 6 14 20 A small amount of rhodium black on the stirring paddle Example 7 21 30 A small amount of rhodium black on the stirring paddle Example 8 11 14 none Comparative Example 1 35 43 Lots of Rhodium Black Comparative Example 2 91 81 Large amount of rhodium black

[0079] Table 2 Catalyst stability evaluation results

[0080]

[0081]

[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A phosphite catalyst system, characterized in that: The invention comprises a rhodium complex catalyst containing a phosphite ligand and a solid stabilizer; the solid stabilizer is an amine-cured epoxy resin.

2. The phosphite catalyst system according to claim 1, characterized in that The phosphite ligand is selected from monodentate phosphites and / or bidentate phosphites.

3. The phosphite catalyst system according to claim 1, characterized in that The phosphite ligand has a structure shown in Formula A and / or Formula B:

4. The phosphite catalyst system according to claim 1, characterized in that The molar ratio of the phosphite ligand to the elemental rhodium in the rhodium complex catalyst containing the phosphite ligand is 1:1 to 20:

1.

5. The phosphite catalyst system according to claim 1, characterized in that It also includes an aldehyde solvent; the mass of the amine-cured epoxy resin is 0.1% to 2% of the total mass of the rhodium complex catalyst containing phosphite ligands and the aldehyde solvent.

6. The phosphite catalyst system according to claim 5, characterized in that The mass concentration of the rhodium complex catalyst containing the phosphite ligand and the element rhodium in the aldehyde solvent is 50-500 ppm.

7. The phosphite catalyst system according to claim 5, characterized in that The aldehyde solvent is selected from one or more of butyraldehyde, valeraldehyde, hexanal and heptanal; And / or, the amine-cured epoxy resin is selected from amine-cured bisphenol F epoxy resin and / or amine-cured bisphenol A epoxy resin.

8. The phosphite catalyst system according to claim 1, characterized in that The rhodium complex catalyst containing the phosphite ligand is prepared according to the following method: Under the condition of synthesis gas, a metal rhodium compound and a phosphite ligand are heated and reacted in an aldehyde solvent to obtain a rhodium complex catalyst containing the phosphite ligand.

9. The phosphite catalyst system according to claim 8, characterized in that The temperature of the heating reaction is 60° C. to 100° C.; the time of the heating reaction is 0.5 to 2 hours; and the pressure of the heating reaction is 1 to 3 MPa.

10. A method for preparing a phosphite catalyst system, characterized in that: The following steps are involved: Under the condition of synthesis gas, the metal rhodium compound and the phosphite ligand are heated to react in an aldehyde solvent, and after cooling, the synthesis gas is discharged and a solid stabilizer is added to obtain a phosphite catalyst system.

Citation Information

Patent Citations

  • A method for preparing aldehydes by olefin hydroformylation reaction, use of phenolic antioxidants and method for improving the stability of catalytic systems

    CN115850041B

  • Hydroformaylation processes

    US5741944A